Pengaruh Kepuasan Gaji dan Kultur Organisasi Terhadap Persepsi Aparatur Pemerintah Daerah Tentang Tindak Korupsi - Firma Sulistyowati (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2007)
The aim of this research is to examine empirically the influence of satisfac¬tion of salary and corporate culture upon the local public servant’s perception towards corruption. The samples of this research are taken from the population of the local public servants in DIY province, especially those who are in the Dinas Kimpraswil, Dinas Pendidikan, Dinas Kesehatan, Dinas Pertanian, Biro Umum Setda, Biro Tata Pemerintahan Setda, Biro Kepegawaian, dan Badan Pengawas Daerah. The data are collected by giving questioner directly to 95 respondents. The analysis unit used in this research is individual analysis. While the hypothesis testing technique used is multiple regression. This technique is aimed at knowing the influence of two independent variables (satisfaction of salary and corporate culture) simultaneously upon one dependent variable (the local public servant’s perception towards corruption.The result of the research shows that the satisfaction of salary partially does not influence upon the local public servant’s perception towards corruption, and corporate culture influences partially upon the local public servant’s perception to¬wards corruption. The testing of hypothesis simultaneously shows that the two inde¬pendent variables influence the local public servant’s perception towards corrup¬tion.Keywords: satisfaction of salary, corporate culture, perception towards corruption, local public services